Early onset myasthenia gravis in a Malawian woman: Challenges in managing myasthenia gravis in a low-resource setting. (July 2021) - Phiri, T; Noah, P; Borgstein, E; Baker, T; Mhemedi, B; Finch, P
Myasthenia gravis is a rare autoimmune disease, which presents with ocular or generalised symptoms. Few publications describe its prevalence in African populations. We describe a young woman who was diagnosed with myasthenia gravis in a Malawian public hospital and outline the challenges encountered in managing this condition in a low-resource setting.